Mapping of genomic EGFRvIII deletions in glioblastoma: insight into rearrangement mechanisms and biomarker development. Issue 10 (12th April 2018) - Koga, Tomoyuki; Li, Bin; Figueroa, Javier M; Ren, Bing; Chen, Clark C; Carter, Bob S; Furnari, Frank B
Abstract: Background: Epidermal growth factor receptor (EGFR) variant III (vIII) is the most common oncogenic rearrangement in glioblastoma (GBM), generated by deletion of exons 2 to 7 of EGFR . The proximal breakpoints occur in variable positions within the 123-kb intron 1, presenting significant challenges in terms of polymerase chain reaction (PCR)–based mapping. Molecular mechanisms underlying these deletions remain unclear. Methods: We determined the presence of EGFRvIII and its breakpoints for 29 GBM samples using quantitative PCR, arrayed PCR mapping, Sanger sequencing, and whole genome sequencing (WGS). Patient-specific breakpoint PCR was performed on tumors, plasma, and cerebrospinal fluid (CSF) samples. The breakpoint sequences and single nucleotide polymorphisms (SNPs) were analyzed to elucidate the underlying biogenic mechanism. Results: PCR mapping and WGS independently unveiled 8 EGFRvIII breakpoints in 6 tumors. Patient-specific primers yielded EGFRvIII PCR amplicons in matched tumors and in cell-free DNA (cfDNA) from a CSF sample, but not in cfDNA or extracellular-vesicle DNA from plasma. The breakpoint analysis revealed nucleotide insertions in 4 samples, an insertion of a region outside of the EGFR locus in 1, microhomologies in 3, as well as a duplication or an inversion accompanied by microhomologies in 2, suggestive of distinct DNA repair mechanisms. In the GBM samples that harbored distinct breakpoints, the SNP compositions of EGFRvIII and amplified non-vIII EGFR were identical, suggesting that these rearrangements arose from amplified non-vIII EGFR . Conclusion: Our approach efficiently "fingerprints" each sample's EGFRvIII breakpoints. Breakpoint sequence analyses suggest that independent breakpoints arose from precursor amplified non-vIII EGFR through different DNA repair mechanisms.